Social assistance performance on local economic development: evidence from island regions in East Indonesia - Amin, Chairullah; Zamzam, Irfan; Reviane, Indraswati Tri Abdi; Duko, Firdaus; Hasnin, Muhammad; Muhammad, Nurdin I; Hartarto, Romi Bhakti; Anwar, Cep Jandi (Jurnal Ekonomi & Studi Pembangunan, 2024)
During economic uncertainty following the COVID-19 pandemic, social assistance is vital for alleviating the economic burden on the poor and vulnerable to poverty, particularly those residing in island-based areas. The research aims to measure the performance of social assistance programs in the regional economy of the North Maluku Archipelago Province. The study employs Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) to measure efficiency values, with input variables including social aid, unemployment, and inflation, while the output variable is poverty. The results reveal that social assistance is ineffective in reducing poverty. Several obstacles, including the minimal budget allocation, inaccuracies in identifying assistance recipients, and insufficient time for aid distribution are identified as primary causes of the inefficiency of social aid programs. Updating poverty data into one unified and integrated dataset is essential for the efficiency distribution of social assistance. Accurate targeting and timely distribution are the keys to the effectiveness of social assistance programs in reducing poverty.